MATHEMATICAL MODEL OF REIMBURSEMENT DECISION MAKING IN RUSSIA. RESULTS OF VIM LIST FOR 2016 - A. S. Kolbin (Фармакоэкономика, 2016)
Background: In 2014 we firstly analyzed the formalized system (points and expert opinions) of drug inclusion and exclusion into the reimbursement lists in Russian Federation. The liner mathematical model of decision making was developed and adopted.Aim. Update the existing model using the results of reimbursement procedures acting from 2106.Material and methods. The linear models developed and adopted in 2014 were used. In 2015 we included data on 141 drug dossiers. We analyzed the decision of the expert body, chief Ministry of Health expert and the final committee decision.Results. 43 new drugs were included into the reimbursement lists acting from 2016. The model of expert body decision had an error 7,09% (12,4% in 2014). The model of chief Ministry of Health expert decision had an error – 7% (10% in 2014). The above mentioned experts became more experienced in the formalized procedure of decision making. The model of final decision had an error about 42% (35% in 2014). Conclusion. Linear models are working tools for modelling reimbursement system decisions. At the mean time the existing system of decision making needs more formalization.